تنمية الذكاء الشخصي كمدخل لتحسين الثقة بالنفس للمعاقين ذهنيا القابلين للتعلم: دراسة وصفية تجريبية - شعبان، عمرو سعيد اسماعيل Shaaban, Amr Said Ismail; منتصر، شادية عبدالعزيز مهتدي; سليمان، سناء محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2017)
هدفت الدراسة إلى الكشف عن فعالية برنامج تدريبي لتنمية الذكاء الشخصي وتحسين الثقة بالنفس للمعاقين ذهنيا القابلين للتعلم، وتكونت عينة الدراسة من عد (20) طفلا من الأطفال المعاقين ذهنيا القابلين للتعلم الملحقين بمدرسة أحمد شوقي للتربية الفكرية بإدارة وسط التعليمية بمحافظة الإسكندرية، قسمت عينة الدراسة إلى مجموعتين: المجموعة التجريبية (10) أطفال، والمجموعة الضابطة (10) أطفال، من الأطفال المعاقين ذهنيا القابلين للتعلم، تراوحت أعمارهم ما بين (9-12)، وتراوحت نسب ذكائهم ما بين (50-70)، واستخدم الباحث في الدراسة المنهج شبه التجريبي ذو المجموعتين، وطبق الباحث علي عينة الدراسة الأدوات التالية: 1- مقياس الذكاء الشخصي (إعداد الباحث) 2- مقياس الثقة بالنفس (إعداد الباحث) 3- البرنامج التدريبي المصمم للدراسة (إعداد الباحث) وأسفرت النتائج عن: 1- توجد علاقة بين الذكاء الشخصي والثقة بالنفس لدى الأطفال المعاقين ذهنيا القابلين للتعلم. 2- يتحسن الذكاء الشخصي لدى أطفال المجموعة التجريبية المعاقين ذهنيا القابلين للتعلم بعد تطبيق البرنامج التدريبي. 3- تتفوق المجموعة التجريبية على المجموعة الضابطة من الأطفال المعاقين ذهنيا القابلين للتعلم في الذكاء الشخصي بعد تطبيق البرنامج. 4- تتحسن الثقة بالنفس لدى أطفال المجموعة التجريبية المعاقين ذهنيا القابلين للتعلم بعد تطبيق البرنامج التدريبي. 5- تتفوق المجموعة التجريبية على المجموعة الضابطة من الأطفال المعاقين ذهنيا القابلين للتعلم في الثقة بالنفس بعد تطبيق البرنامج. 6- يستمر أثر البرنامج التدريبي في تنمية الذكاء الشخصي لدى الأطفال المعاقين ذهنيا القابلين للتعلم بعد مرور فترة شهر على التطبيق. 7- يستمر أثر البرنامج التدريبي في تحسين الثقة بالنفس لدى الأطفال المعاقين ذهنيا القابلين للتعلم بعد مرور فترة شهر على التطبيق. مما يشير إلى فاعلية البرنامج التدريبي في تنمية الذكاء الشخصي، وتحسين الثقة بالنفس لدى الأطفال المعاقين ذهنيا القابلين للتعلم
This study aimed to investigate the effectiveness of the existing training program in developing Personal Intelligence, and enhancing Self - Confidence in Educable Mentally handicapped children, the sample of the study consisted of (20) children from Educable Mentally handicapped children who joined Ahmed Shawky for Mental Education, Alexandria Governorate, The sample is divided into two groups: the experimental group (10) and control group (10) children Educable Mentally handicapped children aging between (9-12) years, and their IQ. Ratios ranged between (50-70), semi-experimental method with Experimental design with two groups, The researcher used the following tools: 1. Personal Intelligence scale (prepared by researcher). 2. Self Confidence scale (prepared by researcher). 3. The Training Program designed to study (prepared by researcher). The results reveal that: 1- There is a correlation between Personal Intelligence and Self Confidence in Educable Mentally handicapped children. 2- Improving personal intelligence in Educable Mentally handicapped children after applying the training program. 3- The Experimental group surpasses the control group in Personal Intelligence in Educable Mentally handicapped children after applying the training program. 4- Improving Self – Confidence in Educable Mentally handicapped children after applying the training program. 5- The Experimental group surpasses the control group in Self – Confidence in Educable Mentally handicapped children after applying the training program. 6- The impact of the training program in the development of personal intelligence, in Educable Mentally handicapped children after a month from the application. 7- The impact of the training program in improving self in Educable Mentally handicapped children after a month from the application. this Indicates to the effectiveness of the training program in developing Personal Intelligence, and enhancing Self – Confidence in Educable Mentally handicapped children.
Keywords: استراتيجيات التعلم -- الذكاء الوجدانى -- الثقة بالنفس -- المعاقون ذهنيا